Mixed layer depth reconstructions based on dinocyst assemblage data for 16 Holocene records in the subpolar North Atlantic using the modern analogue technique and weighted averaging partial least squares - Wu, Xiner; de Vernal, Anne; Allan, Estelle (PANGAEA, 2025)
Winter mixed layer depth (MLD) was reconstructed from 16 previously published records of dinocyst assemblage data using two different approaches: modern analogue technique (MAT) and weighted averaging partial least square (WAPLS) regression and calibration. The n = 1968 modern dinocyst database and the modern MLD climatology of 1981-2010 from the World Ocean Atlas 2018 were used as calibration dataset. The records cover the Holocene and are located in the present-day wintertime deep convection areas of the subpolar North Atlantic. The reconstructions of winter MLD were used to infer changes in the strength of wintertime deep convection during the Holocene. They also allow for comparisons with other proxy records and model simulations.
Keywords: Dinocysts; Holocene; mixed-layer depth; Paleoceanographic proxies; reconstruction; subpolar North Atlantic